Posttraumatic stress disorder and its associated factors among people living in Dabat district, northwest Ethiopia - Melese, Mihret; Maru, Lemlemu; Esubalew, Dereje (Frontiers in Psychiatry, 2024)
Background The conflict between the Ethiopian government and the Tigray People’s Liberation Front (TPLF) in the Dabat district of Ethiopia has led to significant civilian casualties, instances of rape, sexual abuse, and property theft. These traumatic events contribute to the development of post-traumatic stress disorder (PTSD) among local residents. However, there is currently no available data on the prevalence of PTSD and its associated factors in this region. This study seeks to fill this gap by assessing PTSD prevalence and identifying related factors among residents of the war-affected Dabat district in northwest Ethiopia. Method A community-based correctional study was conducted in the Woken and China kebeles of Dabat district, northwest Ethiopia, spanning from July 13 to September 19, 2023. A total of 410 participants were selected using systematic random sampling, making a 100% response rate. The study utilized an interviewer-administered questionnaire, which included the Post-Traumatic Stress Disorder Checklist (PCL-5) to assess PTSD. The research investigated the association between PTSD and various demographic and psychosocial characteristics using both bivariate and multivariable binary logistic regression analyses. Statistical significance was set at a P-value of 0.05. Results The majority of participants in the study were male (62%) with a mean age of 33 ( ± 1.67) years. The overall prevalence of PTSD was 30.7% (95% CI: 26.6–35.10). Multivariable logistic regression analysis identified several factors significantly associated with PTSD: symptoms of depression (AOR=3.5; 95% CI: 1.13-6.89), age between 45 and 67 years (AOR=1.68; 95% CI: 1.04-5.78), experiencing stressful life events (AOR=1.63; 95% CI: 1.05-7.86), experiencing sexual abuse or rape (AOR=1.53; 95% CI: 1.07-6.75), chewing khat (AOR=1.48; 95% CI: 1.08-4.56), being female (AOR=1.43; 95% CI: 1.13-3.67), and having an income of 34.6 USD (AOR=1.28; 95% CI: 1.07-4.67). Conclusion and recommendation This study reported that the prevalence of PTSD was high. As a result, the study suggested that governments and other stakeholders should be involved in implementing efficient interventions and quick measures to mitigate the effects of war on mental health following the conflict. The government and nongovernmental organizations were also advised by these studies to continue providing humanitarian assistance, which should include access to food, clean water, clothing, shelter, and education. This study also suggested that people living in conflict zones should be legally protected from rape, sexual abuse, arson, detention without cause, and kidnapping.